Developing New Materials for Electron Beam Melting: Experiences and Challenges; Materials Science Forum; Vol. 941 : THERMEC 2018 - Koptioug A. V. Andrey Valentinovich; Bekstrom M. Mikael; Botero V. K. A. Vega Karlos Alberto; Popov V. Vladimir; Chudinova E. A. Ekaterina Aleksandrovna (2018, 2018)
Title screen